A comparison of two treatment methods to reduce internal phosphorous cycling in lakes: surface versus injection application - Schütz, Johanna (SLU/Dept. of Aquatic Sciences and Assessment, 2016)
When external nutrients have been reduced from a lake, the internal loading can still be high due to a heavy load of phosphorous (P) in the sediments. Aluminium (Al) treatment has been used for several decades to permanently bind P in sediments to prevent further internal loading. The common method is by surface application of an Al salt. In recent years the method has been developed where a slurry of Al salt is injected directly into the sediments. In this study the efficiency and costs of injection application were compared to previous studies where surface application was used. The results presented in this study indicated that the Al:P ratio in the lakes did differ much, and would thus imply that the binding efficiency is similar for the two application methods. When treatment cost was compared to the amount of P bound by Al in the sediment, the results were also similar, suggesting both methods were equally beneficial for removing excess P from the P cycle in lakes.